Model Pembelajaran Tahfiz Berbasis Metode Tilāwah di MI Muhammadiyah 20 Karangasem Paciran - Saifullah, Jefri; Kholis, Nur; Wibisono, Yusuf (STAI Muhammadiyah Paciran Lamongan, 2025)
This study aims to describe the implementation of the Tilāwah method in improving the Qur’an memorization skills of fifth-grade students at MI Muhammadiyah 20 Karangasem Paciran. The Tilāwah method is an approach that combines repeated reading with an emphasis on tajwid, articulation (makhraj), and the use of melody in memorization. This research employed a descriptive qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. The findings indicate that the Tilāwah method is systematically applied through classical and individual strategies, supported by reinforcement programs such as the playing of murottal audio and group murāja‘ah (review sessions). Evaluation is conducted through pre-tests, post-tests, and periodic tahfiz examinations. Key supporting factors for successful tahfiz learning include student motivation, parental involvement, and the readiness of instructional tools. Challenges encountered include time constraints, low student concentration, and varying memorization abilities. The study concludes that the Tilāwah method is effective in enhancing the quality of students’ Qur’anic memorization, particularly when supported by a structured learning system and a conducive environment.